2022
DOI: 10.1007/s12020-021-02964-y
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage in pheochromocytoma surgery: evaluation of preoperative risk factors

Abstract: Objective Pheochromocytoma surgery carries a higher risk of hemorrhage. Our objective was to identify preoperative risk factors for hemorrhage during pheochromocytoma surgery. Methods Patients who underwent surgery and with postoperative pathological confirmation were enrolled. A total of 251 patients from our center were included in the investigation, and 120 patients from the First Affiliated Hospital, Sun Yat-sen University were included as an external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…In recent years, laparoscopic adrenalectomy has been used more frequently at our center. In fact, a previous study at our center found that between 2002 and 2017, only 77.5% of the patients underwent laparoscopic resection, compared to 92.4% in our study from December 2014 to January 2020 ( 30 ). Consequently, the incidence of intraoperative hemodynamic instability and postoperative complications was lower in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…In recent years, laparoscopic adrenalectomy has been used more frequently at our center. In fact, a previous study at our center found that between 2002 and 2017, only 77.5% of the patients underwent laparoscopic resection, compared to 92.4% in our study from December 2014 to January 2020 ( 30 ). Consequently, the incidence of intraoperative hemodynamic instability and postoperative complications was lower in our study.…”
Section: Discussioncontrasting
confidence: 76%